Buddhist Approach to knowledge Management for Development the Sangha College in upper Northern Thailand - Saithong, Sutthiporn; Provost Sangwornsutkit (Journal of MCU Social Science Review, 2016)
The objectives of this research were 1) to study Buddhist Approach toknowledge Management for development of the Sangha College in upper NorthernThailand., 2) to study the appropriate Buddhist approaches to knowledgemanagement of the local administrative organizations in upper Northern region, and3) to present the Buddhist approaches to Buddhist Approach to knowledgeManagement for Development the Sangha College in upper Northern Thailand.,Research methodology used the mixed methodology, the quantitative and theQualitative Research.The quantitative method is collected data from 20 samples of theAdministrator and officer, purposefully selected with questionnaires, and datawere analyzed by descriptive statistics; frequency, mean and standard deviation.The qualitative research is collected the data from 20 key informants with astructure in-Depth-Interview who were mayors, permanent secretaries andstakeholders, persons The data from both methods were analyzed by inductiveanalysis and descriptive interpretation.The findings showed that:The general setting of knowledge management of the Sangha College inupper Northern region as of human resources development was found thathuman resources must have a chance to be trained, go on educational tours bothdomestic and abroad, and bring back the new knowledge and experience todevelop organizations. For the job development, it was found that there wereparticipatory meeting and team work. There was learning experiences fromeducation tour and technology was used in the organizations to manage data. Asfor the organizational development, it found that knowledge management of citymunicipality abided by official rules, and regulations. Overall, the city municipalityhad basic knowledge of knowledge management and embedded in theorganization, only that it was not systemized.The appropriate Buddhist approaches to the knowledge management oflocal administrative organization in the upper Northern region was that theknowledge management was managed by integrating Aparihaniyadhamma,principles leading to never decline, only to prosperity, to manage the knowledgein organizations and to develop human resource, works, and organizations towardsthe learning organizations such as holding regular meeting, meeting together anddispersing together in harmony. It is the beneficial virtue for organizationaldevelopment, for it helped organizations to be more effective and more efficient.Meanwhile, the knowledge management-related organizations is to take intoaccount the moral and ethical development organizations in order to effectivelyimprove the development effectiveness the work, the human resource, theorganization, and sustainable organizations development.The Buddhist model for knowledge management to develop the localadministrative organizations in Sangha College upper Northern region found that theintegration of Aparihiniyadhamma and was a guidance in knowledge management,and it should have standardized strategic plans for knowledge management. Thereshould be activities for learning exchanges, knowledge banks, knowledgecategorizing for easy access, and activities evaluation to achieve three objectivesknowledge management was very necessary for human resource development. Theshould be activities for learning exchanges, knowledge banks, knowledgecategorizing for easy access, and activities evaluation to achieve three objectiveswhich are; the work development, the human resource development, and theorganization development towards continuous learning organizations.